2015
DOI: 10.1016/j.jep.2015.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Reporting effectiveness of an extract of three traditional Cretan herbs on upper respiratory tract infection: Results from a double-blind randomized controlled trial

Abstract: Compared with placebo the essential-oil extract of three Cretan aromatic plants provided no detectable statistically significant benefit or harm in the patients with upper respiratory illness, although descriptive differences were identified in favorable direction mainly in the virus-positive population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 31 publications
3
62
0
1
Order By: Relevance
“…Sixteen pharmacies, purposively selected, participated as recruiting sites. The preparation of the extract is extensively described elsewhere [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen pharmacies, purposively selected, participated as recruiting sites. The preparation of the extract is extensively described elsewhere [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…Upon presenting at the pharmacies, eligible patients were invited to complete an anonymous questionnaire (Additional file 1 : Questionnaire.doc), developed based on the Wisconsin Upper Respiratory System Survey (WURSS-21), which assessed symptoms’ severity [ 6 ]. This tool has been previously used with reliable results [ 4 ]. Symptoms were recorded at the day of visit at the pharmacy (day 1), as well as at the fourth (day 4) and seventh (day 7) day of extract intake, via phone calls performed by the pharmacists.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with a theoretical framework that was designed a few years back, practice-based research and networking remains restricted [17]. Multiple research projects have already been implemented in examining effectiveness of various interventions carried-out in the primary care setting either through national or European funded projects [18,19]. Networking for research is still lacking and funding for collaborative research from EU is limited in Greece with some exceptions, where the University of Crete and the Cretan practice-based research network is involved (http://fp7restore.eu/, http://euwise.com/, http://www.otcsociomed.uoc.gr/joomla/).…”
mentioning
confidence: 99%
“…Ginseng, a well-known medicinal herb, has been used in traditional medicine for thousands of years, and was found to be effective for treating influenza (Yoo et al, 2012) and HIV (Park et al, 2014); while in a clinical trial, Ginseng was found to help in curing HBV infection (Choi et al, 2016). Ethnopharmacological use of essential oil extract of three traditional Cretan aromatic plants in Eastern Mediterranean region and Near East claimed to be effective in the prevention and treatment of upper respiratory tract infections of bacterial and viral etiology (Duijker et al, 2015). While an Egyptian plant Nigella sativa extract tested against influenza patients showed better activity in people who cannot be treated with interferon-alpha (Barakat et al, 2013).…”
Section: Mode Of Action Of Plant-derived Antiviral Agentsmentioning
confidence: 99%